2023
DOI: 10.1007/s00784-023-05139-3
|View full text |Cite
|
Sign up to set email alerts
|

Are comorbidities associated with the cytokine/chemokine profile of persistent apical periodontitis?

Abstract: Objectives This study aimed to identify disease-related markers in persistent apical periodontitis (PAP) biopsies and examine whether these were associated with comorbidities like rheumatoid arthritis (RA) and cardiovascular diseases (CVD). Materials and method The levels of the cytokines/chemokines GM-CSF, IFN-γ, IL-2, IL-6, IL-9, IL-10, IL-13, IL-15, IL-17E/IL-25, IL-21, IL-23, IL-27, IL-28A/IFN -λ2, IL-33, MIP-3α/CCL20, and TNF-α were determined in lesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Bidirectional interactions exist: the microorganisms affect the host and the host affects the microorganisms. Recent research has investigated the effect of comorbidities, such as rheumatoid arthritis or cardiovascular diseases, with AP and report an association of elevated levels of inflammatory markers: analyses of the levels of cytokine/chemokine markers in AP lesions indicated that these markers may be associated with the differentiation of different T-cell populations (12). Cytokines or chemokines are signaling proteins that control the inflammatory response.…”
mentioning
confidence: 99%
“…Bidirectional interactions exist: the microorganisms affect the host and the host affects the microorganisms. Recent research has investigated the effect of comorbidities, such as rheumatoid arthritis or cardiovascular diseases, with AP and report an association of elevated levels of inflammatory markers: analyses of the levels of cytokine/chemokine markers in AP lesions indicated that these markers may be associated with the differentiation of different T-cell populations (12). Cytokines or chemokines are signaling proteins that control the inflammatory response.…”
mentioning
confidence: 99%